SMEs circular economy practices in the European Union: Multilevel implications for sustainability - Tritto, N.; Dias, J. G.; Bassi, F. (Social Indicators Research, 2024)
This paper examines the willingness of small and medium-sized enterprises (SMEs) in the European Union (EU) to implement Circular Economy (CE) practices, i.e. re-planning the use of water to reduce consumption and maximize reuse, using of renewable energy sources, re-planning energy consumption to reduce its use, reducing waste by recycling or reusing waste or selling it to another company, redesigning products and services to reduce the use of materials or using recycled materials. These aspects are conceived as indicators of the willingness to implement CE practices, which is explained by factors at the company and country levels. The dataset comes from a unique survey involving more than 10,000 SMEs in the EU. This hierarchical structure – companies within countries – was analyzed using a multilevel factor model that takes into account the heterogeneity between countries. The variables at the company-level are: company size (number of employees and total turnover in 2015), company foundation, sector of economic activity, type of clients and goods, and percentage of the turnover invested in R&D. Country-level covariates cover different dimensions of sustainability: per capita GDP, illiteracy rate, waste generation, and corruption perception index. At the levels of company and country, there are factors that explain the attitude towards CE. Finally, factor scores at both levels show a split between Western and Eastern European countries (with few exceptions) regarding the willingness of SMEs to implement CE activities that define the regional implications of EU policies towards CE, in particular in the context of the European Green Deal.